Streamside mobile mesocosms (MOBICOS): A new modular research infrastructure for hydro‐ecological process studies across catchment‐scale gradients. Issue 3 (20th January 2020) - Fink, Patrick; Norf, Helge; Anlanger, Christine; Brauns, Mario; Kamjunke, Norbert; Risse‐Buhl, Ute; Schmitt‐Jansen, Mechthild; Weitere, Markus; Borchardt, Dietrich
Abstract: A key research aim for lotic ecosystems is the identification of natural and anthropogenic pressures that impact ecosystem status and functions. As a consequence of these perturbations, many lotic ecosystems are exposed to complex combinations of nonchemical and chemical stressors. These stressors comprise temperature fluctuations, flow alterations, elevated solute loads or xenobiotics, and all these factors can pose stress upon aquatic ecosystems on different temporal, spatial and biological scales. Factorial experiments are essential to reveal causal relationships especially between combined stressors and their effects in the environment. However, experimental tools that account for the complexity of running waters across different ecosystem compartments, levels of biological organisation, natural or anthropogenic environmental gradients, and replicability are rare. Here we present a new research infrastructure consisting of streamside mobile mesocosms (MOBICOS) that allows analysing the effects of stressors and stressor combinations through multifactorial experiments in near‐natural settings and across anthropogenic pressure gradients. Consisting of eight container‐based running water laboratories operated as bypasses to running surface waters, MOBICOS combines in situ real‐time monitoring of physicochemical and biological parameters with manipulative experiments across ranges of environmental conditions. Different flume types can be set up within MOBICOS to separate and combine different ecosystem compartments (pelagic, epibenthic and hyporheic zones) in a flexible and modular way. Due to its compact design, the MOBICOS units can be shifted easily to particular sites of interest. Furthermore, simultaneous operation of multiple MOBICOS units at different sites allows the integration of natural gradients in multifactorial experiments. We highlight the versatility of the MOBICOS experimental infrastructure with two case studies addressing (a) hydraulic control of lotic biofilms and (b) pollution‐induced community tolerance of biofilms along an environmental gradient. The modular and mobile MOBICOS units have the potential to significantly advance our understanding of causal relationships between natural environmental oscillations, anthropogenic stressors and their combined ecological impacts on lotic aquatic ecosystems beyond existing stream mesocosm approaches.